2006
DOI: 10.1111/j.1471-0528.2006.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of carbetocin versus syntometrine in the management of the third stage of labour

Abstract: Objective Syntometrine is an effective uterotonic agent used in preventing primary postpartum haemorrhage but has adverse effects including nausea, vomiting, hypertension and coronary artery spasm. Carbetocin is a newly developed long-acting oxytocin analogue that might be used as an uterotonic agent. We compare the efficacy and safety of intramuscular (IM) carbetocin with IM syntometrine in preventing primary postpartum haemorrhage.Design Prospective, double-blinded, randomised controlled trial.Setting Delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 16 publications
5
53
0
3
Order By: Relevance
“…Preeclampsia is associated with thrombocytopoenia and coagulopathy, and active management of the third stage [398], avoiding ergometrine (ergonovine maleate), should be performed to avoid postpartum haemorrhage [399][400][401][402][403][404].…”
Section: Commentsmentioning
confidence: 99%
“…Preeclampsia is associated with thrombocytopoenia and coagulopathy, and active management of the third stage [398], avoiding ergometrine (ergonovine maleate), should be performed to avoid postpartum haemorrhage [399][400][401][402][403][404].…”
Section: Commentsmentioning
confidence: 99%
“…The number of women requiring uterotonic intervention (either additional uterotonic agents or uterine massage) was significantly lower in the Carbetocin group (Boucher et al, 2004). Leung et al randomised 329 women to intramuscular Carbetocin and intramuscular syntometrine and found no difference in the decline of haemoglobin two days after delivery (Leung et al, 2006). Although the rate of PPH was lower in the Carbetocin group, it was not statistically significant (Leung et al, 2006).…”
Section: Carbetocinmentioning
confidence: 95%
“…Leung et al randomised 329 women to intramuscular Carbetocin and intramuscular syntometrine and found no difference in the decline of haemoglobin two days after delivery (Leung et al, 2006). Although the rate of PPH was lower in the Carbetocin group, it was not statistically significant (Leung et al, 2006). About 120 women were randomised to Carbetocin and Syntometrine groups had showed lower haemoglobin drop in the Carbetocin group (Nirmala et al, 2009).…”
Section: Carbetocinmentioning
confidence: 99%
“…The authors concluded that carbetocin should be considered a good alternative to conventional uterotonics in preventing postpartum haemorrhage after vaginal delivery. In this retrospective study, carbetocin displayed significantly better uterotonic activity than an oxytocin/ ergometrine combination containing less than half the ergometrine dose contained in syntometrine 27 . However, these findings are still of interest as these retrospective data more closely reflect everyday clinical practice.…”
Section: Carbetocin In Vaginal Deliverymentioning
confidence: 99%
“…However, they remain useful therapeutic options for postpartum haemorrhage treatment when other interventions prove ineffective 21 . Recent interest has focused on the prophylactic use of the oxytocin receptor agonist carbetocin [22][23][24][25][26][27][28][29] . Here we review the most recent clinical data regarding the efficacy of carbetocin in the prevention of postpartum haemorrhage following caesarean section and vaginal delivery, and provide an update on the safety and tolerability in comparison to conventional uterotonic agents.…”
mentioning
confidence: 99%